Community and Species-Level Changes of Insect Species Visiting Mangifera indica Flowers Following Hurricane María: “The Devil Is in the Details” - Cabrera-Asencio, Irma; Meléndez-Ackerman, Elvia J. (Frontiers in Ecology and Evolution, 2021)
Mangifera indica is a widespread economically important tropical fruit. An ongoing study at the Juana Diaz Experimental Station in Puerto Rico aims at understanding the factors that influence local pollination success and fruit yields in four mango cultivars (Keitt, Kent, Tommy Atkins and Julie) at different temporal scales. Here we describe the results of insect collection campaigns that evaluated flower visitor communities of these cultivars in the spring seasons of 2017 (before Hurricane Maria), 2018 (after Hurricane Maria) and 2019 (two year after Hurricane Maria). We expected a reduction in diversity, abundance and yields and even changes in composition following the hurricane events of 2017. Over the three years, plants were visited by a combined total of 50 insect species, mostly Diptera (also the most abundant), Hymenoptera, Coleoptera and Lepidoptera. The relative abundances of insect communities changed but overall species richness of insect communities appeared to be ‘bouncing back’ by 2019. A clear decline in overall plant yields for all cultivars was seen in 2018 but then surpassed pre-hurricane levels for three out of four cultivars in 2019. Trees experienced a global insect abundance increase in 2018 which was sustained in 2019. Two of the most dominant insects, Palpada vineforum and Apis mellifera, showed a “reduction-recovery” pattern for in the period of 2018-2019 but not so for Cochliomyia minina which was very abundant in 2018 but then returned to pre-hurricane levels in 2019. In any given year, mango trees exposed to higher richness and abundance of species experienced higher yields but these relationships were often weaker in 2018 (post-hurricane) and not all cultivars were equally successful at attracting the same levels of diversity and abundance of insects. Our results do support the importance of pollinator diversity to improve agricultural yields. They also indicate that managing pollinators for plant yields within the context of future extreme atmospheric events requires understanding not only how these pollinator communities may recover from these events but also an understanding of how individual pollinators (vs. other factors) may influence plant yields.